Photoredox Fischer Indole Synthesis - Kaga, Atsushi; Fukushima, Tomohiro; Shimokawa, Jun; Kitamura, Masato (Synthesis, 2019)
Visible light photoredox conditions were applied to the traditional Fischer indole synthesis. N,N-Diarylhydrazones were efficiently converted into the corresponding indoles even at 30 °C by treatment with bromotrichloromethane in the presence of Ru(bpy)3Cl2·6H2O as the photocatalyst. Electrochemical study revealed the viability of oxidative quenching cycle for the photocatalysis, which set the basis for proposing the redox-based reaction mechanism.
Keywords: Fischer indole synthesis; [3,3]-sigmatropic rearrangement; photoredox; radicals; hydrazones; cyclic voltammetry